Mechanical behaviour and morphology of thixoformed aluminium alloy reinforced by graphene - Md Ali, Afifah; Omar, Mohd Zaidi; Mohamed, Intan Fadhlina; Wakhi Anuar, Nur Farah Bazilah; Salleh, Mohd Shukor; Hashim, Hanizam (MDPI, 2022)
Thixoforming is a promising method that offers several advantages over both liquid and solid processing. This process utilizes semi-solid behaviour and reduces macrosegregation, porosity and forming forces during the shaping process. Microstructural and mechanical characterization of 0.3, 0.5 and 1.0 wt% graphene nanoplatelet (GNP) reinforced A356 aluminium alloy composite fabricated by thixoforming was investigated. Stir casting was employed to fabricate feedstocks before they were thixoformed at 50% liquid. The microstructure was characterized and evaluated by field emission scanning electron microscopy with an energy dispersive X-ray detector and X-ray diffraction. Mechanical testing, such as microhardness and tensile testing, was also performed to estimate the mechanical properties of the composites. The incorporation of 0.3 wt.% GNPs in Al alloy increased by about 27% in ultimate tensile strength and 29% in hardness. The enhancement in tensile strength is primarily attributed to load transfer strengthening due to the uniform dispersion of these GNPs within the Al matrix, which promotes effective load transfer during tensile deformation, and GNPs’ wrinkled surface structure. Simultaneously, the addition of GNPs enhances the grain refinement effect of the Al alloy matrix, resulting in a grain size strengthening mechanism of the GNPs/Al composites. The results reveal that thixoformed composite microstructure consists of uniformly distributed GNPs, α-Al globules and fine fibrous Si particles. The composites’ grains were refined and equiaxed, and the mechanical properties were improved significantly. This study creates a new method for incorporating GNPs into Al alloy for high-performance composites.